Calculation of the diffusion coefficient of thiophene oligomers using molecular dynamics - Camarada, M. B. (2012)
Electropolymerisation is a very useful methodology for conducting polymers synthesis. A total comprehension of this process will help on the designing of new materials with improved optical and electrical properties. In this sense, computational simulations can deliver important information at atomic scale. Within a kinetic Monte Carlo scheme, diffusion rates are crucial to obtain accurate predictions; however, experimental values of this dynamic property for different oligomers are very scarce among literature. In this study, the diffusion coefficient (D) of thiophene oligomers (1Th-6Th) has been calculated using molecular dynamics simulations coupled with the Einstein expression. Results are in the order of experimental values, demonstrating that this methodology is a fast and reliable alternative to calculate diffusion coefficients with low computational costs. © 2012 Copyright Taylor and Francis Group, LLC.